Self-Citation Analysis of the Most Prolific Author in Halu Oleo University using Fi-Index - Saputri Nur, Wahyuni; Ibrahim, Cecep; Jaya, Asrul; Majidah, Majidah (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study aims to analyze the self-citation behavior of the ten most productive lecturers at Halu Oleo University using a bibliometric approach. Employing the Fi-Index method for self-citation analysis, the research followed three main stages: data collection, data processing, and data analysis. The data were obtained from the Scopus database, focusing on the top ten productive lecturers at the institution. Each lecturer’s self-citation activity was measured using the Fi-Index formula, which compares the number of self-citations relative to their h-index. The findings revealed that all ten lecturers demonstrated self-citation patterns within a normal range. Muhammad Nurdin recorded the highest number of self-citations (867) with a Fi-Index score of 0.047572, followed by Maulidiyah (654, Fi-Index 0.043446), and others with similarly low Fi-Index scores ranging from 0.002096 to 0.043446. These values indicate that their self-citation practices do not exceed what is typically considered acceptable relative to their publication impact. The study concludes that the Fi-Index is a practical tool for evaluating the proportionality of self-citations among academic authors. It is recommended that future research apply the Fi-Index more broadly to assess self-citation behaviors among researchers across institutions and disciplines, ensuring a balanced interpretation of scholarly influence.